PERANCANGAN SISTEM INFORMASI TRACKING DOKUMEN PEMBAYARAN DENGAN METODE WATERFALL BERBASIS WEB DI BANK. ABC - Syafran Nurrahman; M Tafsiruddin; Rizka Ardiantika (Universitas Trilogi, 2026)
ABSTRACT The process of sending payment documents in some institutions is still done via email, which risks the loss of delivery history, the lack of structured tracking recaps, and the difficulty of monitoring the verification flow between teams. Bank ABC faces similar problems in the payment document tracking process that involves several user roles. This study aims to design a web-based payment document tracking information system using the Waterfall System Development Life Cycle (SDLC) system development method. The research methodology used is a descriptive method with a case study approach. The system development stages include needs analysis, system design, coding, testing, and maintenance. The designed system involves three main roles: the operational team, reviewers, and approvers, with different access rights settings at each stage of the process. The results of the study indicate that the information system built is capable of recording, monitoring status, and searching payment documents centrally and in real-time. System testing using the blackbox testing method shows that all main functions of the system run according to user requirements. This system contributes to increasing the effectiveness of payment document management and monitoring at Bank ABC. Keywords: Information System, Payment Document Tracking, Waterfall SDLC, Web Application, Black-Box Testing